A programme for the prevention of post-traumatic stress disorder in midwifery (POPPY): indications of effectiveness from a feasibility study. Issue 1 (1st January 2018) - Slade, Pauline; Sheen, Kayleigh; Collinge, Sarah; Butters, Jenny; Spiby, Helen
ABSTRACT: Background: Midwives can experience events they perceive as traumatic when providingcare. As a result, some will develop post-traumatic stress disorder (PTSD), with adverse implications for their mental health, the quality of care provided for women and the employing organizations. POPPY (Programme for the prevention of PTSD in midwifery) is a package of educational and supportive resources comprising an educational workshop, information leaflet, peer support and access to trauma-focused clinical psychology intervention. A feasibility study of POPPY implementation was completed.Objective: This study aimed to identify potential impacts of POPPY on midwives' understandingof trauma, their psychological well-being and job satisfaction.Method: POPPY was implemented in one hospital site. Before taking part in the POPPY workshop (T1) midwives (N = 153) completed self-report questionnaires, which measured exposure to work-related trauma, knowledge and confidence of managing trauma responses, professional impacts, symptoms of PTSD, burnout and job satisfaction. Measures were repeated (T2) approximately 6 months after training (n = 91, 62%).Results: Midwives' confidence in recognizing (p = .001) and managing early traumaresponses in themselves and their colleagues significantly improved (both p < .001). There was a trend towards reduced levels of PTSD symptomatology, and fewer midwives reported sub clinical levels of PTSD (from 10% at T1 to 7% at T2). The proportion of midwives reporting high and moderate levels of depersonalization towards care was reduced (33% to 20%) and midwives reported significantly higher levels of job satisfaction at T2 (p < .001). Reductions in self-reported stress-related absenteeism (12% to 5%), long-term changes to clinical allocation (10% to 5%) and considerations about leaving midwifery (34% to 27%) were identified.Conclusions: In conclusion, POPPY  shows very positive potential to improve midwives' mental health and the sensitivity of care they provide, and reduce service disruption and costs for trusts. Large-scale longitudinal evaluation is required.